2018
DOI: 10.1097/meg.0000000000001238
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in a European inflammatory bowel disease inception cohort: an Epi-IBD study

Abstract: This study demonstrates the high prevalence of low vitamin D levels in treatment-naive European IBD populations. Furthermore, it demonstrates the presence of low vitamin D levels in patients with IBD who smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
1
23
2
1
Order By: Relevance
“…on 504 IBD patients, of which 80% had been diagnosed with CD, 49.8% were vitamin D deficient ( 23 ). Analysis of vitamin D deficiency in an epidemiological collaboration amongst centers across Europe (Epi-IBD study) including a cohort of 238 patients revealed a prevalence of vitamin D deficiency of 65.4% in CD and 53.7% in UC, and vitamin D insufficiency of 17.3% in CD and 22.3% in UC ( 25 ). Zullow et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…on 504 IBD patients, of which 80% had been diagnosed with CD, 49.8% were vitamin D deficient ( 23 ). Analysis of vitamin D deficiency in an epidemiological collaboration amongst centers across Europe (Epi-IBD study) including a cohort of 238 patients revealed a prevalence of vitamin D deficiency of 65.4% in CD and 53.7% in UC, and vitamin D insufficiency of 17.3% in CD and 22.3% in UC ( 25 ). Zullow et al .…”
Section: Discussionmentioning
confidence: 99%
“…showed association of vitamin D deficiency with mucosal inflammation and disease activity in UC patients ( 30 ). In addition, clinical and biochemical disease activity has also been reported as a factor associated with vitamin D deficiency ( 25 , 31 ). However, in a retrospective study in a single northern German IBD cohort, patients were stratified according to clinical disease activity into highly active (HBI >9 or Simple Clinical Colitis Activity Index (SCCAI) >6) and those in remission (HBI 0-3 or SCCAI 0-2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While its exact pathogenesis is still unclear, studies have shown IBD to be associated with genetic predisposition, combined with a complex variety of environmental influences (e.g., diet, smoking, sleep), in addition to microbial and immune factors [14][15][16]. Vitamin D deficiency is known to occur with increased prevalence in patients with Crohn's disease (CD) and ulcerative colitis (UC), the two predominant pathophysiological manifestations of IBD [17,18]. However, it has yet to be proven whether inadequate vitamin D status acts as a trigger or propagator of inflammation in IBD, whether the deficiency arises purely as a consequence of chronic inflammatory activity or whether there may be some aspects of both.…”
Section: Introductionmentioning
confidence: 99%
“…Bis zu 60% der IBD-Patienten, insbesondere Patienten mit der Diagnose MC und erhöhter Krankheitsaktivität [72, 193, 194] sowie Schwangere mit IBD, leiden an Vitamin-D-Mangel [195]. Interessanterweise besitzen junge männliche Patienten ein sehr hohes Risiko [141], und MC-Patienten mit isolierter Kolonbeteiligung bzw.…”
Section: Fehlernährungunclassified